Anterior open bite and its relationship with dental arch dimensions and tongue position during swallowing and phonation in individuals aged 8–16 years: A retrospective case–control study (2020)
bjective > To determine the relationship between AOB and factors such as dental arch dimensionsand tongue position during swallowing and phonation.Material and Methods > A case–control study was performed in two groups: 132 children withAnterior Open Bite (AOB) and 132 with normal vertical overbite (NVO), aged 8-16 years selectedfrom the records taken by a previous study from five public schools. Dental arch dimensions wereassessed through digitalized study models. Swallowing was evaluated using the Payne technique,and phoniatric assessment included an adaptation of the articulation test used to describe pho-nemes. Statistical analysis: Chi-Square or Fisher's exact test for comparisons between qualitativevariables and the Mann Whitney or T-student were applied to compare the dental arch dimensionsaccording to bite type. A logistic regression model was applied to control the effect of confusionbetween independent variables and to describe its simultaneous effect on the type of bite.Results > Intercanine, interpremolar and intermolar widths showed higher values in AOB patientswith a mean deviation (MD) of 0.536 (P = 0.031), 0.60 (P = 0.043) and 1.15, (P < 0.001) respec-tively. Distortions caused by tongue interposition and thrust, tongue protrusion during swallowing,mandibular arch intermolar width, total maxillary arch length, maxillary arch perimeter, andposterior arch depth accounted for 64.6% of AOB and allowed for correct predictions in 83.8% ofthe cases observed in the study population.